Perceptions of tech-based mental health screening - Sacha A McBain; Kylie Cleavenger; Chelsey Bull; Nalin Payakachat; Melody Greer (Trauma Surgery & Acute Care Open)
Background An estimated one-third of patients experience post-traumatic stress disorder (PTSD) or depression in the year following a traumatic injury. The American College of Surgeons requires postinjury PTSD and depression screening in trauma centers, although implementation has been limited. Tech-based solutions have been proposed to improve uptake of postinjury mental health screening. The goals of this pilot study were to assess the usability and acceptability of Blueprint, a tech-based mental health screening platform, and explore attitudes toward tech-based screening and intervention.Methods This pilot study included trauma patients (n=10) admitted to the trauma service. Participants completed the PTSD Checklist-5 and Patient Health Questionnaire-9 using Blueprint to test usability and acceptability of the platform. Participants completed the System Usability Scale (SUS) and a semi-structured interview to assess several domains including attitudes toward tech-based screening, potential barriers to implementation, and its usefulness in a postinjury context. Summative Template Analysis, a data abstraction procedure, was used to analyze qualitative data.Results Blueprint received an average SUS score of 93.25/100 suggesting participants found the interface to be an ‘excellent’ means to assess postinjury mental health concerns. Participants were supportive of universal screening and identified several benefits to engaging in tech-based routine monitoring of postinjury PTSD and depressive symptoms including convenience, personalization, and trauma-informed care. Regarding intervention, patients valued web-based psychoeducation on topics related to their overall care and local resources.Conclusions Tech-based mental health screening was highly usable and valuable to trauma patients at risk for postinjury PTSD and depression. Participants valued web-based psychoeducation and resources, but overall preferred Blueprint be used to facilitate access to in-person mental health services. Further evaluation of Blueprint as a means of assessment, intervention, and referral is needed.